Self-reported antibiotic stewardship and infection control measures from 57 intensive care units: An international ID-IRI survey - El-Sokkary, Rehab; Erdem, Hakan; Kullar, Ravina; Pekok, Abdullah Umut; Amer, Fatma; Grgic, Svjetlana; Rello, Jordi (Elsevier Science London, 2022)
We explored the self-reported antibiotic stewardship (AS), and infection prevention and control (IPC) activities in intensive care units (ICUs) of different income settings. A cross-sectional study was conducted using an online questionnaire to collect data about IPC and AS measures in participating ICUs. The study participants were Infectious Diseases-International Research Initiative (IDI-IR) members, committed as per their institutional agreement form. We analyzed responses from 57 ICUs in 24 countries (Lower-middle income (LMI), n = 13; Upper-middle income (UMI), n = 33; High-income (HI), n = 11). This represented (similar to 5%) of centers represented in the ID-IRI. Surveillance programs were implemented in (76.9%-90.9%) of ICUs with fewer contact precaution measures in LMI ones (p = 0.02); (LMI:69.2%, UMI:97%, HI:100%). Participation in regional antimicrobial resistance programs was more significantly applied in HI (p = 0.02) (LMI:38.4%,UMI:81.8%,HI:72.2%). AS programs are implemented in 77.2% of institutions with AS champions in 66.7%. Infectious diseases physicians and microbiologists are members of many AS teams (59%&50%) respectively. Unqualified healthcare professionals(42.1%), and deficient incentives(28.1%) are the main barriers to implementing AS. We underscore the existing differences in IPC and AS programs' implementation, team composition, and faced barriers. Continuous collaboration and sharing best practices on APM is needed. The role of regional and international organizations should be encouraged. Global support for capacity building of healthcare practitioners is warranted. (C) 2022 Published by Elsevier Ltd on behalf of King Saud Bin Abdulaziz University for Health Sciences.
Keywords: Multidrug resistance; Infection control; Stewardship; Low- and upper-middle and high income; MDROs; Pan drug resistance